Physical, Mechanical, and Adhesive Properties of Novel Self-Adhesive Resin Cement - Long Ling; Yumeng Ma; Yulin Chen; Raj Malyala (International Journal of Dentistry)
Objective. To evaluate a newly developed self-adhesive resin cement on physical, mechanical, and adhesive properties and compare it with other commercial self-adhesive resin cements. Materials and Methods. Experimental self-adhesive resin cement (SARC) was formulated by our proprietary adhesive resin and filler technology. Maxcem Elite, RelyX Unicem 2, SpeedCem Plus, SmartCEM 2, and Calibra Universal 2 were selected for comparison. Working and setting times, film thickness, water sorption and solubility, flexural strength, and modulus were measured in accordance with ISO-4049. Consistency was tested according to modified ISO 4823. Shear bond strengths were conducted according to ISO 29022. The data were analyzed by one-way ANOVA and post hoc Tukey’s tests (p ≤ 0.05). Results. All cements showed about 2–4 min working time and about 3–6 min setting time except that RelyX Unicem 2 has a longer working time (9’58”) and setting time (10’18”). All cements meet ISO standards for film thickness (≤50 µm), water sorption (≤40 µg/mm3) except Maxcem Elite (46.19 µg/mm3), and water solubility (≤7.5 µg/mm3) except SmartCEM 2 (11.35 µg/mm3) and Calibra Universal (9.87 µg/mm3). Experimental SARC showed significantly higher flexural strength and modulus than other cements (p < 0.001). For self-curing, Experimental SARC has statistically higher bond strength than other cements (p < 0.001) except statistically the same as RelyX Unicem 2 (p > 0.05). For light-curing, Experimental SARC showed significantly higher bond strength than other cements (p < 0.001) except statistically the same as Maxcem Elite and RelyX Unicem 2 (p > 0.05). For dual-curing, the bond strength of Experimental SARC is significantly higher than that of other cements (p < 0.001). Conclusion. The newly developed self-adhesive resin cement exhibited favorable bonding capability and physical and mechanical properties compared to other commercial self-adhesive resin cements and is a good option for cementation of indirect restorations with potential long-term clinical success.